A Prospective, Randomized Comparison Between Perivascular and Perineural Ultrasound-Guided Axillary Brachial Plexus Block. Issue 5 (1st September 2012) - Bernucci, Francisca; Gonzalez, Andrea P.; Finlayson, Roderick J.; Tran, De Q.H.
Abstract : Background: This prospective, randomized, observer-blinded study compared perivascular (PV) and perineural (PN) ultrasound-guided axillary brachial plexus block (AXB) for upper extremity surgery. Methods: Fifty patients were randomly allocated to receive a PV (n = 25) or PN (n = 25) ultrasound-guided AXB. The local anesthetic agent (lidocaine 1.5% with epinephrine 5 μg/mL) and total volume (32 mL) were identical in all subjects. For both groups, the musculocutaneous nerve was first located and then anesthetized using 8 mL. Subsequently, in the PV group, 24 mL was deposited dorsal to the axillary artery (6-o'clock position). In contrast, for the PN group, the median, ulnar, and radial nerves were individually anesthetized with volumes of 8 mL. During the performance of the block, the performance time, number of needle passes, and complications (vascular puncture, paresthesia) were recorded. Subsequently, a blinded observer assessed the onset time, block-related pain scores, and success rate (surgical anesthesia). The main outcome variable was the total anesthesia-related time (sum of performance and onset times). Results: No differences were observed between the 2 groups in terms of success rate (92%–96%), total anesthesia-related time (27.1–29.0 min), and block-related pain scores. However, the PV technique required fewer needle passes (3.5 [SD, 1.0] vs 8.2 [SD, 2.2]; P = 0.000) as well as a shorter performance time (8.2 [SD, 2.3] vs 15.7 [SD, 3.2] min; P = 0.000) and was associated with a lower incidence of paresthesia (8 vs 52%; P = 0.001). In contrast, the PN technique resulted in a quicker onset time (13.8 [SD, 7.0] vs 18.9 [SD, 7.0] min; P = 0.021) and a decreased incidence of vascular puncture (0 vs 24%; P = 0.01). Conclusions: Perivascular and PN ultrasound-guided AXBs result in comparable success rates and total anesthesia-related times. Because of fewer needle passes and a shorter performance time, the PV technique provides a simple alternative for ultrasound-guided AXB.